STUDI KOMPARASI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DAN TAI TERHADAP PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 1 RAMBAH - Husnul Rezki Putri; Susilawati '; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of research was to know whether there was significant difference for student’s achievement between the application of the TGT and TAI models on the topic of hydrocarbon in class X Senior High School 1 Rambah and to know the cooperative learning that has been gave the best result to student’s achievement between TGT and TAI models. The kind of research was the experiment research with Randomized Pretest-Posttest Comparison Group Design. There were three classes as population, X.E, X.F and X.G. There were two classes as sample of research which were choiced randomly by using normality and homogenity test. The result, class X.F as the experiment that used TGT model and class X.E as the experiment that used TAI model. The data analysis technique used to test hypothesis was the t-test of two side. The result of analysis showed that there was no significant difference the student’s achievement between the application of TGT and TAI models (tobserved = -1,428 and ttable = 2,00). The test of N-gain normalized showed that students achievement between TGT and TAI models was high category with valued 0,76 and 0,81. So, the TGT and TAI models as good as to improve the student’s achievement.Key Words: Comparative Study, Student’s Achievement, Teams Games Tournament (TGT), Team Assisted Individualization (TAI), Hydrocarbon